Penentuan Interval Waktu Perawatan Komponen Kritis pada Mesin Turbin di PT PLN (Persero) Sektor Pembangkit Ombilin - Taufik; Selly Septyani (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2015)
Electrical energy requirements in Indonesia annually increase in line with economic growth and an increase in population. So, PT PLN (Persero) have to be able to fulfill the public demands for electrical energy. One of the power generation existed is Steam PowerGeneration. The condition of power generation depended on the maintenance, so, well maintenance made power plant operated at ease condition. Production process in SteamPower Generation of Ombilin used a closed cycle or continuous process. If a machine or an equipment damaged, it will stop the whole function. In the production process, the company involved several main engines are boiler, turbine, condenser, and generator. But the damage often occurs in turbine engine which caused the generation power in Steam PowerGeneration of Ombilin can not operate. Therefore, it needs a maintenance action of machinery/equipment to be able to prevent the damage. The right strategy to keep the engine operating is determining the optimal maintenance interval of equipment for minimizing downtime.The stages of this research begin by determining the critical engine with Criticality Analysis method. Then, the determination of the critical components using Pareto diagram. Then, the determination of the probability density function (pdf) and the reliability of critical components. After that, the determination of maintenance intervals of the critical components by using the criterion of minimizing the downtime that will be used to make maintenance scheduling.Based on the processing data has been done, it was found that the critical engine is a turbine engine with a total value is 44 and the critical components of a turbine engine are membrane turbine, bearing and turning gear with the examination time interval for each critical component are 960.48 hours (40 days), 908.57 hours (37 days) and 1150.28 hours (48days). While the preventive replacement intervals for components of turbine membrane is after operating for 3410 hours, the replacement for bearing components can be carried out during overhaul after operating for 8000 hours and the replacement intervals for components of turning gear is after operating for 4500 hours. The reliability values for each critical component before and after preventive maintenance remains the same, but the value of downtime on each component decreases. The total values of availability for each critical component exceeds 95%.